Of online edition and the mixed facets of diseases in the developing world - Borodo, M. M. (Nigerian Journal of Basic and Clinical Sciences, 2026)
The Editorial Board welcomes you to the first online edition of the Nigerian Journal of Basic and Clinical Sciences. While hard copies of the journal would continue to be available, we hope that this online facility would not only allow for quick access to the journal articles as well as offloading new articles for publication at the journal website, but it would also allow for faster online review of articles by our reviewers. At this juncture, we would like to acknowledge the support and cooperation of our new publishers, Wolters Kluwer | Medknow, of India. In this edition, Ochicha and colleagues in their article on inflammatory cervical smears and infections concluded, as others have, that inflammation in the smears (seen in 50% of patients) did not correlate well with the frequency of infections(seen in 30% of patients), thereby making the use of this investigation problematic for gynecologists.